Uniform radial positive electrode material precursor and preparation method thereof

The preparation of uniformly radial positive electrode material precursors through two-stage co-precipitation method has solved the problems of uneven particle morphology and unstable internal structure in the prior art, and achieved a high-performance ternary positive electrode material, which is suitable for large-scale industrial production.

CN119706978AInactive Publication Date: 2025-03-28HENAN KELONG NEW ENERGY CO LTD

Patent Information

Application Number
CN202510208693.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the preparation process, the existing ternary positive electrode material precursors have problems such as uneven particle morphology, unstable internal structure and lack of precise regulation in the preparation process, which affects the compaction density, cycle stability and rate performance of the material.

Method used

A uniformly radial positive electrode material precursor was prepared by a two-stage co-precipitation method. By accurately controlling reaction conditions such as pH, ammonia content and gas ratio, a unique structure of the core layer and shell layer was formed.

Benefits of technology

The uniform radial growth of precursor particles is achieved, the mechanical strength and electrochemical properties of the material are improved, the cycle stability and rate performance are enhanced, the production cost is reduced, and the large-scale industrial production is adapted to large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706978A_ABST
    Figure CN119706978A_ABST
Patent Text Reader

Abstract

The invention discloses a uniformly radial positive electrode material precursor and a preparation method thereof. The cross section of the uniformly radial positive electrode material precursor is uniformly radial, and the shape of the uniformly radial positive electrode material precursor is divided into a core and an outer layer, the core is loose and porous, and the outer layer is in a regular radial shape; the method adopts a coprecipitation method to carry out two-stage reaction preparation, in the first reaction stage, an inner core layer is prepared; a second reaction stage: preparing a shell layer to reach a target particle size; the secondary particle D50 is 6.0-14.0 microns, the TD is greater than 1.90 g / cm, and the BET is less than or equal to 14m < 2 > / g; the precursor is small in structure core and compact in outer layer, particles grow in a radial mode from inside to outside, lithium ions can be separated and embedded out easily, the particle structure is more stable, and excellent rate performance and cycling stability are shown; a staged coprecipitation method is adopted, and controllable growth of a particle structure is realized by accurately controlling the ratio of oxygen to nitrogen and reaction conditions; according to the whole process design, the complex parameter adjusting range is reduced, and the production stability and repeatability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, and in particular to a uniform radial positive electrode material precursor and a preparation method thereof. Background Art

[0002] With the rapid development of the global new energy vehicle market, the demand for high energy density lithium-ion batteries is increasing. The cathode material in lithium-ion batteries is an important component that determines its performance. Among them, ternary cathode materials (NCM, NCA) have become the focus of current research and industrialization due to their high energy density and excellent electrochemical properties. However, the performance of cathode materials depends largely on the quality and structural characteristics of their precursors.

[0003] In the prior art, ternary precursor materials are usually prepared by coprecipitation; by controlling the ratio of nickel, cobalt and manganese metal ions, precursors with different properties can be obtained; high nickel precursors can improve the energy density of the battery because the increase in nickel content helps to improve the reversible capacity of the material. During the preparation process, the reaction conditions, including reaction temperature, pH value, stirring speed, etc., need to be strictly controlled to obtain precursor particles with uniform particle size and high tap density; however, in the actual preparation process, the traditional method still has the following technical problems: 1. Uneven particle morphology: The precursor particles generated in the existing process often show a wide particle size distribution and irregular morphology, which affects the compaction density and cycle stability of the material; 2. Unstable internal structure: The primary grains are disordered, or there is a problem of uneven grain orientation, resulting in discontinuous lithium ion diffusion paths, thereby limiting the rate performance and cycle life of the material; 3. Lack of precise control of the preparation process: The traditional coprecipitation process is not precise enough in controlling reaction conditions (such as temperature, pH value, atmosphere, etc.), which can easily lead to excessive particle growth or structural defects.

[0004] The Chinese patent announcement number is CN116111079A, which discloses a radial porous structure of nickel-cobalt-manganese hydroxide precursor and its preparation method. The chemical formula of the precursor is NixCoyMn1-xy(OH)2, which significantly improves the rate of lithium ion insertion / extraction and enhances the electrochemical properties of the material, but also has the following shortcomings: First, some process steps still require the use of high-concentration ammonia water (up to 12 mol / L), which brings a burden to environmental protection and wastewater treatment, and limits green and sustainable development; second, the preparation process requires frequent adjustment of pH value and ammonia concentration, and relies on complex operations such as overflow and concentration, which places high requirements on equipment precision and production control, and is not conducive to large-scale industrial application.

[0005] Chinese Patent Application No. 202110696601.0 discloses a high-nickel cathode material and its preparation method, which includes three reaction stages: coprecipitation reaction, growth reaction in the first stage, and growth reaction in the second stage. The defect is that parameters such as pH value, complexing agent concentration, and stirring rate need to be precisely controlled in each reaction stage, increasing the operation difficulty; during the sintering process, Li / Ni mixing phenomenon is likely to occur, resulting in a decrease in the crystal structure stability, and performance deterioration may be caused by overfiring or grain growth. The multi-stage process has a strong dependence on process parameters, increasing the risk of inconsistent performance between batches.

[0006] Chinese Patent Application No. 202311363870.0 discloses a sodium-ion battery cathode precursor and its preparation method. Although the core-shell structure design enhances the stability of the material, the boundary between the core layer and the shell layer is likely to cause interface effects, which may lead to discontinuity in the lithium / sodium ion diffusion path. The core-shell structure requires two independent precipitation reactions, and each reaction has high requirements for conditions.

[0007] In view of the above problems, the present invention provides a uniformly radial cathode material precursor and its preparation method. Summary of the Invention

[0008] The technical problem to be solved by the present invention is to overcome the existing defects, provide a uniformly radial cathode material precursor and its preparation method, and utilize two reaction processes to solve the problems of uneven radial distribution and wide distribution of the precursor cross-section. The core loose porous structure alleviates the stress caused by volume change, and the regular radial morphology of the outer layer enhances the mechanical strength of the particles, making the overall particles show higher stability during the cycling process, avoiding the occurrence of cracks and deformation, and effectively solving the problems in the background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: A uniformly radial cathode material precursor and its preparation method, the chemical formula of the precursor is Ni x Co y Mn 1-x-y (OH) 2 、Ni x Co y Al 1-x-y (OH) 2 or Ni x Co y Mn z Al (1-2x-2y-2z) / 3 (OH) 2 , where 0.50 < x < 0.95, 0.01 < y < 0.25, 0.01 < z < 0.25. The overall morphology of the precursor is secondary particles formed by the aggregation of primary grains, the cross-section is uniformly radial, and the secondary particle D 50 is 6.0 - 14.0 μm.

[0010] Furthermore, the precursor is divided into an inner core layer and an outer shell layer, the inner core layer is loose and porous, and the outer shell layer is radially regular in shape.

[0011] Furthermore, the precursor has a tap density TD>1.90 g / cm³ and a specific surface area BET≤14m² / g, which optimizes the compaction characteristics and energy density of the material, and is conducive to meeting the use requirements of high-performance lithium-ion batteries.

[0012] Furthermore, the method adopts a coprecipitation method to carry out a two-stage reaction preparation, in which the inner core layer is prepared in the first reaction stage; and the outer shell layer is prepared in the second reaction stage to achieve the target particle size; the method comprises the following steps: Step S1, preparing a mixed salt solution of transition metal nickel salt, cobalt salt, manganese salt and / or aluminum salt, preparing an alkali solution as a precipitant solution, and preparing an ammonia solution as a complexing agent solution; Step S2, first reaction stage: add deionized water to the reactor, the volume of which accounts for 40-60% of the volume of the reactor, heat the reactor, stir at a rate of 350-600 r / min, introduce nitrogen, and prepare a reaction base liquid; Step S3, when the oxygen content is lower than 0.5%, the complexing agent solution, the precipitant solution and the metal salt solution are simultaneously pumped into the reaction kettle, and oxygen is introduced, the ratio of oxygen to nitrogen in the mixed gas is 1-5:30, the pH value of the mixed solution is controlled to be 11.0-13.0, the ammonia content is 0.50-3.50 g / L, the reaction time is 25-65 h, and an inner core layer is generated; Step S4, second reaction stage; add deionized water to the reactor, the volume of which accounts for 40-60% of the volume of the reactor, heat the reactor, stir at a rate of 250-500 r / min, introduce nitrogen, prepare the reactor bottom liquid, the pH is required to be 10.0-11.5, and the ammonia content is required to be 2.5-5.5 g / L; Step S5, the inner core layer material obtained by the first stage reaction is put into the reactor through a mass flow meter or weighing, and the complexing agent, precipitant and metal salt solution are simultaneously injected into the reactor, and oxygen is introduced at the same time. The ratio of oxygen to nitrogen in the mixed gas is 1-5:30. After reaching the target particle size, the feeding is stopped. The reaction time is 20-60h. The precursor is obtained through aging, centrifugal washing, drying, screening and iron removal processes.

[0013] Through the staged reaction process, the present invention realizes the precise control of the precursor particle size, making the D 50 This precise particle size distribution, which is stable within the range of 6.0-14.0 μm, improves material uniformity and reduces batch-to-batch variation.

[0014] Furthermore, the metal salt solution is one of nickel-cobalt-manganese, nickel-cobalt-manganese-aluminum, nickel-cobalt-aluminum or nickel-manganese-aluminum, the molar concentration of total metal in the metal solution is 1.0-2.5 mol / L, the alkali solution concentration is 6-10 mol / L, and the ammonia solution concentration is 4.5-5.5 mol / L.

[0015] Furthermore, the core layer is obtained in the first stage of the reaction; the input amount of the material in the first stage of the reaction is calculated according to the target particle size, and the processing is carried out by injecting it with a mass flow meter or testing the solid content of the slurry by weighing.

[0016] Furthermore, oxygen and nitrogen need to be introduced simultaneously in the first reaction stage and the second reaction stage.

[0017] Furthermore, the reaction temperature of the first reaction stage and the second reaction stage is 40-70°C.

[0018] Furthermore, both the first reaction stage and the second reaction stage are produced in an intermittent manner, wherein the diameter of the outer shell layer is 3-6 times the diameter of the inner core layer.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The precursor particles grow radially from the inside to the outside, which is conducive to the diffusion of lithium salts in the precursor particles during the sintering process, and the reaction is more complete. The prepared ternary positive electrode material can form a lithium ion diffusion channel from the inside to the outside. This radial structure is conducive to the entry and exit of lithium ions, and the particle structure is more stable, thus showing excellent electrochemical properties, excellent rate performance and output power. At the same time, the two reaction processes are used to solve the problem of radial unevenness and wide distribution of the precursor cross section.

[0020] 2. The present invention adopts a staged co-precipitation method, and realizes the controllable growth of the particle structure by accurately controlling the ratio of oxygen and nitrogen and the reaction conditions; the entire process design reduces the complex parameter adjustment range and improves the stability and repeatability of production; at the same time, the process uses more economical chemical reagents to reduce production costs and provide good adaptability for large-scale industrial production.

[0021] 3. The present invention adopts a uniform radial particle structure design to make the precursor have a unique morphology of loose and porous core and regular radial outer layer; this structure that grows radially from the inside to the outside effectively forms a fast transmission channel for lithium ions, significantly improving the rate performance of the material; at the same time, the loose porous structure of the core alleviates the stress caused by volume change, and the regular radial morphology of the outer layer enhances the mechanical strength of the particles, so that the overall particles show higher stability during the cycle and avoid the occurrence of cracks and deformation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1Cross-sectional view of Embodiment 1 of the present invention; Figure 2 SEM image of Comparative Example 1 of the present invention. Detailed implementation manners

[0023] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] Please refer to Figure 1-2 , the present invention provides a technical solution: a uniformly radially distributed cathode material precursor and a preparation method thereof. The chemical formula of the precursor is Ni x Co y Mn 1-x-y (OH) 2 、Ni x Co y Al 1-x-y (OH) 2 or Ni x Co y Mn z Al (1-2x-2y-2z) / 3 (OH) 2 , where 0.50 < x < 0.95, 0.01 < y < 0.25, 0.01 < z < 0.25. The overall morphology of the precursor is secondary particles formed by the aggregation of primary grains, and the cross-section is uniformly radially distributed. The diameter D 50 of the secondary particles is 6.0 - 14.0 μm.

[0025] The precursor is divided into a core layer and a shell layer. The core layer is loose and porous, and the shell layer has a regular radial shape.

[0026] The tap density TD of the precursor is > 1.90 g / cm³, and the specific surface area BET ≤ 14 m² / g.

[0027] This method is prepared by a two-stage reaction using the co-precipitation method. In the first reaction stage, the core layer is prepared; in the second reaction stage, the shell layer is prepared to reach the target particle size. The method includes the following steps: Step S1, prepare a mixed salt solution of transition metal nickel salt, cobalt salt, manganese salt and / or aluminum salt, prepare an alkali solution as a precipitating agent solution, and prepare an ammonia water solution as a complexing agent solution; Step S2, the first reaction stage: add deionized water to the reaction kettle, and the volume accounts for 40 - 60% of the volume of the reaction kettle. Heat up the reaction kettle, the stirring rate is 350 - 600 r / min, introduce nitrogen gas, and prepare the reaction bottom liquid; Step S3, when the oxygen content is lower than 0.5%, the complexing agent solution, the precipitant solution and the metal salt solution are simultaneously pumped into the reaction kettle, and oxygen is introduced, the ratio of oxygen to nitrogen in the mixed gas is 1-5:30, the pH value of the mixed solution is controlled to be 11.0-13.0, the ammonia content is 0.50-3.50 g / L, the reaction time is 25-65 h, and an inner core layer is generated; Step S4, second reaction stage; add deionized water to the reactor, the volume of which accounts for 40-60% of the volume of the reactor, heat the reactor, stir at a rate of 250-500 r / min, introduce nitrogen, prepare the reactor bottom liquid, the pH is required to be 10.0-11.5, and the ammonia content is required to be 2.5-5.5 g / L; Step S5, the inner core layer material obtained by the first stage reaction is put into the reactor through a mass flow meter or weighing, and the complexing agent, precipitant and metal salt solution are simultaneously injected into the reactor, and oxygen is introduced at the same time. The ratio of oxygen to nitrogen in the mixed gas is 1-5:30. After reaching the target particle size, the feeding is stopped. The reaction time is 20-60h. The precursor is obtained through aging, centrifugal washing, drying, screening and iron removal processes. Example 1

[0028] Prepare solution: prepare nickel, cobalt and manganese ternary metal salt solution, the metal molar ratio in the solution is Ni:Co:Mn=0.92:0.05:0.03, and the total metal concentration is 1.9 mol / L; prepare sodium hydroxide solution with a concentration of 8 mol / L as a precipitant; prepare ammonia solution with a concentration of 5 mol / L as a complexing agent.

[0029] First reaction stage: Deionized water was added to a 100 L reactor, with the water volume accounting for 40% of the total volume of the reactor as the reaction base liquid; the reactor was heated to 60°C, the stirring speed was set to 500 r / min, nitrogen was introduced, and the oxygen content was controlled to be less than 0.5%; at the same time, the metal salt solution, the precipitant and the complexing agent were added to the reactor at a fixed flow rate, and oxygen was introduced, and the ratio of oxygen to nitrogen was adjusted to 1:30, the pH value of the mixed solution was maintained at 12.3, and the ammonia concentration was 5 g / L; when the particle size reached 2.05 μm (about 45 hours of reaction), the feeding was stopped, the first reaction stage was terminated, and the core layer was obtained.

[0030] Second reaction stage: Deionized water was added to the same reactor, and the water volume was 60% of the total volume of the reactor as the reaction base liquid; the temperature was raised to 60°C, the stirring speed was set to 350r / min, and nitrogen was introduced; the core particles prepared in the first stage were added to the reaction base liquid according to a predetermined proportion; at the same time, the metal salt solution, the precipitant and the complexing agent were added to the reactor at a fixed flow rate, and oxygen was introduced, and the ratio of oxygen to nitrogen was adjusted to 1:6, the pH value of the mixed solution was maintained at 11.4, and the ammonia concentration was 4.5g / L; when the particle D50 reached 12μm (about 50 hours of reaction), the feeding was stopped and the second reaction stage was ended; after the reaction was completed, the material was aged for 12 hours.

[0031] After the residual ions are removed by centrifugal washing, the filter cake is dried at 120°C, sieved and iron-removed to finally obtain a uniform radial cathode material precursor; secondary particles D 50 The particle size is 12 μm, the tap density (TD) is 2.05 g / cm³, and the specific surface area (BET) is 13.5 m² / g.

[0032] Comparative Example 1 A nickel-cobalt-manganese ternary metal salt solution is prepared, wherein the molar ratio of Ni:Co:Mn in the nickel-cobalt-manganese ternary metal salt solution is 0.85:0.14:0.01; the concentration of the nickel-cobalt-manganese ternary metal salt solution is 1.9 mol / L, a sodium hydroxide solution with a concentration of 8 mol / L is prepared as an alkali solution, and an ammonia solution with a concentration of 5 mol / L is prepared; Deionized water was added to a 100L reactor, the volume of which was 40% of the volume of the reactor, and a reaction base solution was prepared. The reactor was heated to 50°C, the stirring rate was 550r / min, and nitrogen was introduced. The complexing agent, the precipitant and the three metal salt solutions were simultaneously injected into the reactor, and oxygen was introduced. In the mixed gas, the ratio of oxygen to nitrogen was 1:15, the pH of the mixed solution was controlled to be 13.0, and the ammonia content was controlled to be 3.5g / L. After a certain reaction time, the flow rates of the complexing agent, the precipitant and the three metal salt solutions were adjusted to make the pH of the mixed solution 11.60, the ammonia content 4.0g / L, the reaction time 60h, and the particle size D 50 The feed was stopped at 12.3μm. After aging, centrifugal washing, drying, screening and iron removal, the precursor obtained had a tap density (TD) of 2.03g / cm³ and a specific surface area (BET) of 13.0m² / g. Example 2

[0033] For the optimized preparation of the precursor particle size, the solution configuration is as follows: the molar ratio of the nickel, cobalt and manganese ternary metal salt solution is Ni:Co:Mn= 0.85:0.10:0.05, and the total metal concentration is 2.0 mol / L; the precipitant and complexing agent are 10 mol / L sodium hydroxide solution and 4 mol / L ammonia solution, respectively.

[0034] First reaction stage: The reactor was heated to 50°C, the stirring speed was set to 400 r / min, nitrogen was introduced, and the oxygen content was less than 1%; the pH value of the mixed solution was maintained at 12.0, and the ammonia concentration was 4 g / L until the core particle size reached 1.8 μm. The reaction time was about 30 hours.

[0035] Second reaction stage: The base solution conditions were adjusted to a pH of 10.5 and an ammonia concentration of 3.5 g / L; the outer layer reaction was continued for 35 hours, and the final particle size D50 was 10 μm.

[0036] After centrifugal washing, the target particles were dried at 100°C; secondary particles D 50 The particle size is 10 μm, the tap density (TD) is 2.00 g / cm³, and the specific surface area (BET) is 12.0 m² / g. Example 3

[0037] Precursor preparation with consistent particle size is achieved by adjusting the oxygen ratio. In the two reaction stages, the ratio of oxygen to nitrogen is 1:10 and 1:5, respectively. The uniformity of radial growth of particles is improved by adjusting the oxygen ratio.

[0038] Precursor D 50 The particle size is 9μm, the tap density (TD) is 1.95g / cm³, and the specific surface area (BET) is 11.0m² / g.

[0039] After aging, washing and drying, the particles have a regular radial structure and show good rate performance and cycling stability. Example 4

[0040] Use low ammonia concentration (3.0-4.0 g / L) process to reduce the impact on the environment.

[0041] Preparation process: The first and second stages both adopted low ammonia process, controlled pH values ​​at 11.5 and 10.5 respectively, and maintained ammonia concentration at 3.0 g / L; the total reaction time was 80 hours, and the final particle D 50 The particle size is 11μm, the tap density (TD) is 2.00 g / cm³, and the specific surface area (BET) is 11.5m² / g; it reduces the cost of waste liquid treatment and meets the requirements of green manufacturing.

[0042] The basic principles, main features and advantages of the present invention are shown and described above. Without departing from the spirit and scope of the present invention, the present invention may also be subject to various changes and improvements, which all fall within the scope of the present invention to be protected.

Claims

1. A uniform radial cathode material precursor, characterized in that: The chemical formula of the precursor is Ni x Co y Mn 1-x-y (OH)2, Ni x Co y Al 1-x-y (OH)2 or Ni x Co y Mn z Al (1-2x-2y-2z) / 3 (OH)2, where 0.50 < x < 0.95, 0.01 < y < 0.25, 0.01 < z < 0.

25. The overall morphology of the precursor is secondary particles formed by the aggregation of primary grains, with a cross-section呈均匀放射状 (uniformly radial), and the secondary particle D 50 is 6.0 - 14.0 μm.

2. The uniform radial positive electrode material precursor according to claim 1, characterized in that: The precursor is divided into an inner core layer and an outer shell layer. The inner core layer is loose and porous, while the outer shell layer is radial in regular shape.

3. The uniform radial positive electrode material precursor according to claim 1, characterized in that: The tap density of the precursor is TD>1.90 g / cm³, and the specific surface area is BET≤14m² / g.

4. A method for preparing a uniform radial positive electrode material precursor according to any one of claims 1 to 3, characterized in that: The method adopts a coprecipitation method to carry out a two-stage reaction preparation. In the first reaction stage, an inner core layer is prepared; in the second reaction stage, an outer shell layer is prepared to achieve a target particle size. The method comprises the following steps: Step S1, preparing a mixed salt solution of transition metal nickel salt, cobalt salt, manganese salt and / or aluminum salt, preparing an alkali solution as a precipitant solution, and preparing an ammonia solution as a complexing agent solution; Step S2, first reaction stage: add deionized water to the reactor, the volume of which accounts for 40-60% of the volume of the reactor, heat the reactor, stir at a rate of 350-600 r / min, introduce nitrogen, and prepare a reaction base liquid; Step S3, when the oxygen content is lower than 0.5%, the complexing agent solution, the precipitant solution and the metal salt solution are simultaneously pumped into the reaction kettle, and oxygen is introduced, the ratio of oxygen to nitrogen in the mixed gas is 1-5:30, the pH value of the mixed solution is controlled to be 11.0-13.0, the ammonia content is 0.50-3.50 g / L, the reaction time is 25-65 h, and an inner core layer is generated; Step S4, second reaction stage; add deionized water to the reactor, the volume of which accounts for 40-60% of the volume of the reactor, heat the reactor, stir at a rate of 250-500 r / min, introduce nitrogen, prepare the reactor bottom liquid, the pH is required to be 10.0-11.5, and the ammonia content is required to be 2.5-5.5 g / L; Step S5, the inner core layer material obtained by the first stage reaction is put into the reactor through a mass flow meter or weighing, and the complexing agent, precipitant and metal salt solution are simultaneously injected into the reactor, and oxygen is introduced at the same time. The ratio of oxygen to nitrogen in the mixed gas is 1-5:

30. After reaching the target particle size, the feeding is stopped. The reaction time is 20-60h. The precursor is obtained through aging, centrifugal washing, drying, screening and iron removal processes.

5. The method for preparing a uniform radial positive electrode material precursor according to claim 3, characterized in that: The metal salt solution is one of nickel-cobalt-manganese, nickel-cobalt-manganese-aluminum, nickel-cobalt-aluminum or nickel-manganese-aluminum. The molar concentration of the total metal in the metal solution is 1.0-2.5 mol / L, the concentration of the alkali solution is 6-10 mol / L, and the concentration of the ammonia solution is 4.5-5.5 mol / L.

6. The method for preparing a uniform radial positive electrode material precursor according to claim 3, characterized in that: The core layer is obtained in the first stage of the reaction; the input amount of the material in the first stage of the reaction is calculated according to the target particle size, and the processing is carried out by injecting with a mass flow meter or testing the solid content of the slurry by weighing.

7. The method for preparing a uniform radial positive electrode material precursor according to claim 5 or 6, characterized in that: In the first reaction stage and the second reaction stage, oxygen and nitrogen need to be introduced simultaneously.

8. The method for preparing a uniform radial positive electrode material precursor according to claim 3, characterized in that: The reaction temperature of the first reaction stage and the second reaction stage is 40-70°C.

9. The method for preparing a uniform radial positive electrode material precursor according to claim 4, characterized in that: Both the first reaction stage and the second reaction stage are produced in an intermittent manner, wherein the diameter of the outer shell layer is 3-6 times the diameter of the inner core layer.

Citation Information

Patent Citations

  • A high-nickel cathode material and its preparation method

    CN113161529B

  • Nickel-cobalt-manganese hydroxide precursor with radial porous structure and preparation method of nickel-cobalt-manganese hydroxide precursor

    CN116111079A

  • Sodium ion battery positive electrode precursor and preparation method thereof

    CN117342628A

  • Precursor with hydroxide coated on outer layer of single crystal and preparation method of precursor

    CN114436342A

  • Nickel-cobalt-manganese precursor based on core-shell structure, positive electrode material and preparation methods of nickel-cobalt-manganese precursor and positive electrode material

    CN115180659A

Cited By

  • High-nickel ternary precursor as well as preparation method and application thereof

    CN120646927A

  • Preparation method of solid-state battery positive electrode material precursor with multi-layer segmented structure

    CN121317908A

  • High-specific-surface-area high-tap-density small-particle ternary precursor and preparation method thereof, positive electrode material and lithium ion battery

    CN121536984A

  • Large-particle positive electrode material precursor, positive electrode material and application thereof

    CN121823673A

  • Preparation method of radial order type ultra-high nickel positive electrode material precursor

    CN122586155A